Percutaneous silicon catheter insertion into the IVC, following percutaneous nephrostomy (PCN) exchange - Kotb, Ahmed F; Elabbady, Ahmed; Mohamed, Khaled; Atta, Mohamed Adel (Canadian Urological Association Journal, 2013)
Percutaneous nephrostomy (PCN) has been widely used to drain an infected, obstructed kidney. Few major complications have been associated with it. Few publications have reported the misplacement of nephrostomy tube into the inferior vena cava (IVC), following percutaneous nephrolithotomy. We report a case of a misplaced silicon catheter, through the left renal vein, extending into the IVC, following nephrostomy tube exchange. Our case was safely managed, and we concluded that although PCN and nephrostomy tube exchange are relatively simple procedures, they should be done cautiously, by a well-trained urologist, and preferably under ultrasound or fluoroscopic guidance.